2020
DOI: 10.1038/s41598-020-70613-x
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF ultra for rapid diagnosis of extrapulmonary tuberculosis in a high-income low-tuberculosis prevalence setting

Abstract: the diagnosis of extrapulmonary tuberculosis (eptB) is often challenging due to paucibacillary nature of the disease. Xpert MtB/Rif Ultra (Ultra) has been developed to improve detection of Mycobacterium tuberculosis complex (Mtc) in paucibacillary specimens. the objective of the study was to assess the performance of Ultra for the diagnosis of eptB in a high-income low tB prevalence country. extrapulmonary samples received for tB diagnostics at two hospitals in norway between January 2015 and January 2016 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…In patients of different ages and in different clinical specimens, Ultra sensitivities ranged from 90 to 95%, and specificities ranged from 86 to 99% [7][8][9] . We did not perform a comparison between Xpert and Ultra, as Xpert is no longer available in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…In patients of different ages and in different clinical specimens, Ultra sensitivities ranged from 90 to 95%, and specificities ranged from 86 to 99% [7][8][9] . We did not perform a comparison between Xpert and Ultra, as Xpert is no longer available in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the software cannot provide information about RIF resistance, it is relevant in the clinical context of the patient. The Global Laboratories Initiative (guidelines), and the working group of Stop TB Partnership, states that "trace category should be considered as a true-positive result for use in clinical decisions and patient follow-up in case of extrapulmonary samples 22 ." However, there is also uncertainty surrounding the interpretation of this category.…”
Section: Discussionmentioning
confidence: 99%
“…In low TB prevalent settings, even a small reduction in specificity could increase the rate of false positive cases. For this reason, Ultra should be performed on pre-selected samples with a high clinical suspect of TB disease [18]. In other studies, it has been reported that the increase in sensitivity with Ultra respect Xpert, specifically in patients with a history of TB [12] [22] and patients with meningitis [23] came at the expense of a decrease in specificity.…”
Section: Discussionmentioning
confidence: 99%